2010
DOI: 10.1111/j.1469-7610.2010.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of quality of care: effects of perinatal HIV infection and early institutional rearing on preschoolers’ attachment and indiscriminate friendliness

Abstract: Etiology and function of indiscriminate friendliness may differ for family-reared versus institution-reared children. The findings of this study suggest the necessity of early interventions improving the quality of care for HIV-infected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 27 publications
3
51
2
5
Order By: Relevance
“…The lack of contingent interactions with a stable caregiver may be related to decreased emotional and behavioral control, including effortful attention regulation and inhibitory control (Bakermans-Kranenburg et al, in press;Dobrova-Krol, Bakermans-Kranenburg, van IJzendoorn, & Juffer, 2010). …”
Section: Theoretical Basis For Investigating Post-institutional Outcomentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of contingent interactions with a stable caregiver may be related to decreased emotional and behavioral control, including effortful attention regulation and inhibitory control (Bakermans-Kranenburg et al, in press;Dobrova-Krol, Bakermans-Kranenburg, van IJzendoorn, & Juffer, 2010). …”
Section: Theoretical Basis For Investigating Post-institutional Outcomentioning
confidence: 99%
“…Children rarely, if ever, experience warm, sensitive, contingently responsive interactions, and there is little opportunity to form an attachment relationship (The St. Petersburg-USA Orphanage Research Team, 2005Team, , 2008 . Indeed, many institutional children are classified as having disorganized attachments (Dobrova-Krol et al, 2010;The St. Petersburg-USA Orphanage Research Team, 2008;Vorria, et al, 2003;Zeanah, Smyke, Koga, & Carlson, 2005). Thus, research with these children can more specifically address the impact of early social-emotional deprivation, rather than other factors often associated with institutions, on later outcomes.…”
mentioning
confidence: 99%
“…Studies focusing on HIV and attachment are mostly focused on attachment styles of adults with HIV (Feeney & Raphael, 1992;Koopman et al, 2000) or the attachment relationships of HIV-positive children (Dobrova-krol, Bakermans-Kranenburg, Van IJzendoorn, & Juffer, 2010). Only one study could be found on mother-infant attachment relationships where the mothers were HIV positive.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple investigations indicate that institutional care is associated with high rates of insecure and disorganized attachment patterns (Dobrova-Krol, Bakermans-Kranenburg, Van Ijzendoorn, & Juffer, 2010;St. Petersburg-USA Orphanage Research Team, 2008;Vorria et al, 2003;Zeanah & Gleason, 2015;Zeanah, Smyke, Koga, Carlson, & the BEIP Core Group, 2005), limited attention has been paid to formal attachment disorders.…”
Section: Introductionmentioning
confidence: 99%